Strategi Pengelolaan Keuangan bagi Generasi Sandwich (Upaya Mewujudkan Ketahanan Finansial Keluarga) di Kecamatan Mijen Kota Semarang - Muchayatin Muchayatin; Parju Parju; Sulistyani Sulistyani; Joko Riyanto; Setyobudi Setyobudi; Siti Aminah; Ribut Musprihadi (Institut Nalanda, 2026)
This community service program aims to improve financial literacy among the sandwich generation in Mijen District, Semarang City - a group that simultaneously shoulders the financial responsibilities of three generations. The program adopted a research-based educational approach involving 92 respondents, with the 40-30-20-10 income allocation method serving as the primary intervention tool. Implementation was carried out across four stages: situational analysis, pre-test, an educational workshop with hands-on simulation, and post-test evaluation. The results revealed that participants' average financial literacy scores rose by 83.7% following the intervention, with the most notable gain observed in the emergency fund formation indicator, which reached 116%. These findings affirm that a simulation-based educational approach can meaningfully shift community financial behavior, particularly in managing day-to-day spending and building financial reserves. To sustain these gains, the program recommends ongoing community mentoring as a long-term strategy for reinforcing financial discipline well beyond the workshop itself.